Considerations on zero‐degree cellulite. (13th November 2021) - Hexsel, Doris; Valente Bezerra, Indira; Mosena, Gabriela; Hexsel, Camile
Abstract: Cellulite affects almost all women, and it is characterized by surface relief alterations, mainly located on the thighs and buttocks, and other areas. Whereas depressed lesions occur due to the presence of thick subcutaneous fibrous septa that pull the skin surface down, raised areas result from the projection of underlying fat to the skin surface. We support that the absence of cellulite can be defined as the ideal balance between the mechanical forces that act between the subcutaneous structures, such as fat and fibrous septa and muscles, and the overlying skin.